Pengujian Calendar Effect di Bursa Efek Indonesia tahun 2016 - Mega Noerman Ningtyas (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2017)
Market efficiency theory stated that stock prices reflect all information in the market. There are 3 different level of market efficiency: weak form, semi-strong form and strong form. When a market is in the state of weak form, there is no investor can gain abnormal return using past information. Calendar effect that is Day of the Week, January Effect and Turn of the Month is anomaly in the stock market that opposed the efficiency market theory. The purpose of this study is to examine the Calendar Effect in Indonesia Stock Exchange during 2016. This research use daily stock price data in LQ45. Using the OLS regression with 5 dummy variables, the results showed that trading day had an effect on stock return where negative return occurred on Monday but not significant. The positive return occured in the following days and the highest return occurred on Wednesday. It can be concluded that the first hypothesis of Day of the Week phenomenon is supported. OLS regression with 1 variable dummy for return in January and 0 otherwise, the result shows that the coefficient is negative and insignificant so it can be concluded that January Effect is not supported. Third hypothesis, Turn of the Month, result shows positive and significant coefficient at level 1%. It means the stock returns in 5 trading days at the end of the month and 2 trading days at the beginning of the month are higher than in other days.